Rare Case of Large Catecholamine Secreting Ganglioneuroma in an Asymptomatic Elderly - Soundarajan, Tivya; Mohamed Badrulnizam Long Bidin; Rajoo, Subashini; Yunus, Rosna (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Ganglioneuromas (GNs) are benign tumors that originate from neural crest cells, composed mainly of mature ganglion cells. These tumors, which are usually hormonally silent, tend to be discovered incidentally on imaging tests and occur along the paravertebral sympathetic chain, from the neck to the pelvis and occasionally in the adrenal medulla. Rarely, GNs secrete catecholamines.1 Adrenal GNs occur most frequently in the fourth and fifth decades of life, whereas GNs of the retroperitoneum and posterior mediastinum are usually encountered in younger adults.2 Adrenal GNs are commonly hormonally silent and asymptomatic; even when the lesion is of substantial size.3 We report an incidentally detected asymptomatic case of an adrenal ganglioneuroma with mildly elevated urinary catecholamine levels in an elderly male. After preoperative alpha blockade, the patient underwent open right adrenalectomy. Upon microscopic examination, the right adrenal mass proved to be a ganglioneuroma, maturing type and the immunohistochemistry examination showed immunoreactivity to synaptophysin, chromogranin, and CD 56, while S100 was strongly positive at the Schwannian stroma. Following resection, catecholamine levels normalized, confirming the resected right adrenal ganglioneuroma as the source of the catecholamine excess. This case represents a rare presentation of catecholamine-secreting adrenal ganglioneuroma in the elderly.